ENDOMORFISMA L0 DARI BCH-ALJABAR - Citra, Restia Sarasworo; ., Suryoto (MATEMATIKA, 2013)
BCH-algebras is an algebraic structure which built on a commutative group. In BCH-algebra there is a mapping from this structure to itself which calledÂ a BCH-endomorphism. In BCH-algebra context, we denote L as a set of all left mapping and it contains L0 which the only non-identity BCH-endomorphism in L with some properties : the left map L0 is a center of BCH-endomorphism, L0 both be a periodic mapping dan an epimorphism on BCH-algebra. Such as a group with the fundamental group homomorphism theorem, in a BCH-algebra we have a fundamental BCH-algebra homomorphism theorem.